Exploring Meinong's Jungle and Beyond The Sylvan Jungle - Volume 1 - Routley, Richard (Synthese Library, Studies in Epistemology, Logic, Methodology, and Philosophy of Science ;, 2018)
In this first volume of The Sylvan Jungle, the editors present a scholarly edition of the first chapter, "Exploring Meinong's Jungle," of Richard Routley's 1000-plus page book, Exploring Meinong's Jungle and Beyond. Going against the Quinean orthodoxy, Routley's aim was to support Meinong's idea that we can truthfully refer to non-existent and even impossible objects, like Superman, unicorns and the (infamous) round-square cupola on Berkeley College. The tools of non-classical logic at Routley's disposal enabled him to update Meinong's project for a new generation. This volume begins with an Introduction from Dominic Hyde, "The 'Jungle Book' in Context," an essay that situates Exploring Meinong's Jungle and Beyond historically. We provide the original Preface by Routley, followed by Chapter 1: "Exploring Meinong's Jungle and Beyond." In Chapter 2, Nicholas Griffin argues that Sylvan's project was insufficiently radical with his essay, "Why the Original Theory of Items Didn't (Quite) Go Far Enough." Sylvan revisits his position from this time in Chapter 3, with his article, "Re-Exploring Item-Theory." Filippo Casati, who has worked in the Routley Archives then takes up the question of the future of Sylvan's research program in his essay, "The Future Perfect of Exploring Meinong's Jungle." Iconic and iconoclastic Australian philosopher Richard Routley (né Sylvan) published Exploring Meinong's Jungle and Beyond in 1980. This work has fallen out of print, yet without great fanfare it has influenced two generations of philosophers and logicians.